Locusts: no time to lower the guard - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Constant vigilance is needed, now as in the past, to avoid locust invasions, which are by nature, erratic.